The Impact of the Low Quality of Teachers on the Learning Process Results of School Accreditation in Manggarai Regency Indonesia - Tapung, Marianus (Ridwan Institute, 2024)
In 2021, Manggarai Regency had 20 schools targeted for BAN S/M NTT accreditation. This accreditation process evaluates school services based on key components such as the quality of graduates, the learning process, teacher quality, and school management, utilizing 36 core assessment points. Our research centers on understanding the intricate relationship between teacher quality components and the learning process. Employing a cross-analysis and a concise descriptive approach, we identified both positive and negative impacts within each component, either directly or indirectly. Utilizing a descriptive-qualitative method, we scrutinized accreditation results documents and conducted cross-cutting analyses to discern these impacts. Our findings revealed a significant connection between the components of teacher quality and the learning process. Specifically, the subpar performance of teachers in points 22 and 21 directly influenced the students' activeness, ability, and skills during the learning process (as evident in points 12 and 15). The primary objective of this research is to delve into this relationship between accreditation components and offer strategic solutions to address the identified negative impacts. In adhering to the research objectives, we maintain brevity in presenting the methods and results, prioritizing a focused exploration of the relationship between teacher quality components and the learning process.